Design of an Expander for Internal Power Recovery in Cryogenic Cooling Plants. (December 2015) - Giovannelli, A.; Archilei, E.M.
Abstract: The electrical power consumption of refrigeration plants is evaluated to be in the order of 15% of the total electricity consumption worldwide. For this reason, many efforts are spent in the development of energy saving techniques to be applied to refrigeration and air conditioning systems. This paper deals with the development of a device which allows an internal recovery in cryogenic plants, reducing their power consumption. Such a device consists in a Compressor-Expander Group (CEG) developed on the basis of automotive turbocharging technology. According to the rules of the similarity theory, a preliminary CEG design has been realized modifying commercially available components. The critical CEG component is the expander. In order to address the new requirements, a turbocharger expander wheel has been strongly modified and equipped with supersonic variable nozzles, designed to have a radially inflow full admission. To verify the performance of such a machine and suggest improvements, a numerical fluid dynamic model has been set up. The commercial Ansys-CFX software has been used to perform steady-state 3D CFD simulations. In this paper all the numerical results are presented, compared with available experimental data and discussed.